2013
DOI: 10.9738/intsurg-d-13-00029.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Prognostic Factors That Are Influential in the Survival and Prognosis of Lung Adenocarcinomas and Invasive Predominant Subtypes

Abstract: Therapeutic approaches to lung adenocarcinomas differ because of their heterogeneous morphologies, prognoses, and clinical features. For this reason, new histopathologic classifications for lung adenocarcinomas were done by the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society to form subtypes with homogeneous prognoses. There are limited clinical data in the literature on the prognosis of the subgroups formed according to the new classification. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The prognostic impact of pathologic invasiveness and the need to predict pathologic invasiveness have been described in many studies. Histologic subtypes defined by IASLC/ATS/ERS classification and other pathologic factors such as lymph node involvement and pleural and vessel invasion are known to show correlation with the survival outcome [ 14 , 15 ]. Consequently, in the clinical setting accurate prediction of pathologic invasiveness may aid the decision for an appropriate operation type based on the status of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic impact of pathologic invasiveness and the need to predict pathologic invasiveness have been described in many studies. Histologic subtypes defined by IASLC/ATS/ERS classification and other pathologic factors such as lymph node involvement and pleural and vessel invasion are known to show correlation with the survival outcome [ 14 , 15 ]. Consequently, in the clinical setting accurate prediction of pathologic invasiveness may aid the decision for an appropriate operation type based on the status of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Major lung resection has been recommended as a standard procedure for the treatment of lung adenocarcinoma, but according to recent literature limited surgical resection could be used instead for cases of small-sized lung cancer [ 16 20 ]. Meanwhile, some studies have emphasized the importance of stratifying early-stage NSCLC patients to select candidates for adjuvant therapy [ 14 , 15 ]. The presence of the micropapillary or solid subtype has been shown to be a poor prognostic factor for overall survival and for recurrence in patients with NSCLC [ 21 , 22 ] and Travis et al [ 21 ] suggested that micropapillary or solid predominant subtype predicts improved responsiveness to adjuvant chemotherapy compared with acinar or papillary predominant tumors in patients with surgically resected lung adenocarcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%